2016
DOI: 10.1039/c6ra14428d
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the anti-breast cancer potential of flavonoid analogs

Abstract: In the course of our search for new antitumor agents for breast cancer, novel flavone derivatives were synthesized, characterized and examined for their antitumor activities against breast cancer cell lines.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…The developed NPs have shown effective anticancer activity by 77 µg as ED 50 whereas the Gloriosasuperba leaf extract showed the ED 50 value at 80 µg. The studies thus demonstrated NPs to be environment friendly to deliver the potential active drugs against triple negative breast cancer (33).…”
Section: Gloriosasuperba Mediated Nanoparticlesmentioning
confidence: 91%
“…The developed NPs have shown effective anticancer activity by 77 µg as ED 50 whereas the Gloriosasuperba leaf extract showed the ED 50 value at 80 µg. The studies thus demonstrated NPs to be environment friendly to deliver the potential active drugs against triple negative breast cancer (33).…”
Section: Gloriosasuperba Mediated Nanoparticlesmentioning
confidence: 91%
“…Several natural products have proved to be potent sources of anti-cancer drugs, as cancer is one of the leading causes of death worldwide ( Butler, 2004 ; Ghosh et al, 2014 ). As a result of the continuous exploration of traditional Chinese medicine, medicinal plants have emerged as a unique treatment strategy for cancer, primarily due to their accessibility, low toxicity, and well tolerated nature ( Takebe et al, 2011 ; Thakor et al, 2016 ). Natural bioactive compounds, especially flavonoids, have a significant impact on the treatment of cancer.…”
Section: Therapeutic Effects Of Taxifolinmentioning
confidence: 99%
“…Briefly, the cells were pre-treated with 2.5 μg/ml of methanol extract for 20 h. The media was removed and washed once with PBS and incubated with DCFH-DA solution (20 μM/well) for 30 min. The cells were then treated with 1000 μM of H 2 O 2 for 6 h. Finally, at the end of the 6 th h, the fluorescence intensity (FI) of DCF was measured in a microplate reader with an excitation wavelength of 485 nm and an emission wavelength of 535 nm [17].…”
Section: Ros Measurement By Dcfh-damentioning
confidence: 99%